1993
DOI: 10.1172/jci116630
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil-mediated fungistasis against Histoplasma capsulatum. Localization of fungistatic activity to the azurophil granules.

Abstract: Human neutrophils (PMN) demonstrated potent fungistatic activity against Histoplasma capsulatum (Hc) yeasts in a sensitive microassay that quantifies the growth of yeasts by the incorporation of 13Hjleucine. At a PMN:yeast ratio of 1:2, PMN inhibited the growth of yeasts by 37%. Maximum inhibition of 85% to 95% was achieved at a PMN/yeast ratio of 10:1 to 50:1. Opsonization of the yeasts in fresh or heat-inactivated serum was required for PMN-mediated Previous studies in vitro have generated conflicting resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 45 publications
2
65
0
2
Order By: Relevance
“…These results are consistent with previous studies that have suggested that Histoplasma yeasts are impervious to the effects of toxic oxygen metabolites generated by human and murine Mø (3,16,34,52). The data also are consistent with the fact that all of the very potent fungistatic activity exhibited by human neutrophils against H. capsulatum yeasts is mediated by the azurophil granules, and the production of toxic oxygen metabolites is not required for neutrophil fungistatic activity (38).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with previous studies that have suggested that Histoplasma yeasts are impervious to the effects of toxic oxygen metabolites generated by human and murine Mø (3,16,34,52). The data also are consistent with the fact that all of the very potent fungistatic activity exhibited by human neutrophils against H. capsulatum yeasts is mediated by the azurophil granules, and the production of toxic oxygen metabolites is not required for neutrophil fungistatic activity (38).…”
Section: Discussionsupporting
confidence: 83%
“…In vitro studies in human Mø (3,38,43) and in murine Mø (16,52) demonstrate that H. capsulatum yeasts are inherently resistant to toxic oxygen metabolites of the respiratory burst. Thus, although the respiratory burst may be stimulated during phagocytosis, H. capsulatum yeasts readily replicate in these cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitation of fungistatic activity against H. capsulatum yeasts. The fungistatic activity of the various azurophil granule components was quantified by the incorporation of [ 3 H]leucine into remaining viable yeasts (23). Viable H. capsulatum yeasts (5 ϫ 10 3 in 0.1 ml) were added to the wells of a 96-well tissue culture plate and were incubated with 0.1 ml of various concentrations of individual components of neutrophil azurophil granules.…”
Section: Methodsmentioning
confidence: 99%
“…The role of cathepsins in host defenses to this fungus is poorly understood. Cathepsin G inhibits, but does not kill, H. capsulatum yeast cells (71). Thus, it seems unlikely that Boc-D-FMK subverts protective immunity by a direct alteration of cathepsin activity.…”
Section: Figurementioning
confidence: 99%